Plasmatic hemostasis at very high altitude - a thrombelastometric approach - Micaela Tobler; Christos Nakas; Matthias Hilty; Andreas Huber; Tobias Merz; Jacqueline Hefti (University of Applied Sciences in Tarnow, Poland, 2021)
Introduction: Changes in blood coagulation during exposure to high altitude are not well understood and studies of activation and consumption of specific coagulation factors in hypoxic humans have yielded conflicting results. In this study we used thrombelastometry (TEM) which allows a global evaluation of clot formation and lysis process to study blood coagulation profiles in volunteers exposed to prolonged hypobaric hypoxia at extreme altitudes. Material and methods: We conducted a prospective observational study in 39 healthy volunteers during a research expedition up to an altitude of 7050 m. Plasma based thrombelastometric measurements and standard coagulation parameters were performed at different altitudes. Results: TEM measurements showed an increase in clotting time (CT) and maximum clot firmness (MCF) at high altitudes, paralleled by an increase in international normalized ratio (INR) and activated partial thromboplastin time (aPTT). Fibrinogen concentration increased until 6022 m. D-Dimer and Thrombin-Antithrombin complex (TAT) increased with time exposed to severe hypoxia. For both measurements high-est levels were found at 4844 m after acclimatization; in contrast, lower values were observed again at 7050m in the group of summiteers. Activated protein C resistance (APC-R) was slightly lowered at all altitudes. Conclusion: Our results suggest that activation of the coagulation and fibrinolytic system occurs with increasing hypobaric hypoxia with concurrent use of coagulation factors indicating the occurrence of a consumption-coagulopathy phenotype.